Biomedical Engineering Letters - Lee, Sang-Hoon.; Lee, Jae Sung.; SpringerLink (Online service) (Korea : The Korean Society of Medical and Biological Engineering : Imprint: The Korean Society of Medical and Biological Engineering, co-published with Springer.)
Biomedical Engineering Letters (BMEL) aims to present the innovative experimental science and technological development in the biomedical field as well as clinical application of new development. The article must contain original biomedical engineering content, defined as development, theoretical analysis, and evaluation/validation of a new technique. BMEL publishes the following types of papers: original articles, review articles, editorials, and letters to the editor. All the papers are reviewed in single-blind fashion.
Keywords: Medicine; Biophysics; Biological physics; Biomedical engineering; Biomedical Engineering and Bioengineering; Biological and Medical Physics, Biophysics; Biomedicine, general; Medical and Radiation Physics